Qualitative Analysis of Valeriana officinalis leaf by Thin-Layer Chromatography - A. Yu. Fisiuk; O. V. Mushkina; N. S. Golyak; O. A. Yorshyk (Регуляторные исследования и экспертиза лекарственных средств)
INTRODUCTION. Drugs based on rhizomes with roots of valerian (Valeriana officinalis L., family Valerianaceae) have sedative, antiarrhythmic, antispasmodic, anticonvulsant, anxiolytic effects and are widely used in psychoemotional and cognitive disorders, for the treatment of dysfunctions of the autonomic nervous system, including children, also for menopausal disorders. Biologically active compounds are contained not only in the underground, but also in the aboveground organs of the plant. This indicates the expediency of studying the qualitative chemical composition of valerian officinalis leaves to assess the possibility of use in medicine, subsequent standardization and the development of new phytopreparations based on them.AIM. Comparative phytochemical analysis of biologically active substances of leaves and rhizomes with roots of Valeriana officinalis by thin-layer chromatography.MATERIALS AND METHODS. Objects of research: leaves and rhizomes with roots of valerian harvested in various districts of the Minsk region of the Republic of Belarus in August 2023, dried by air-shade drying, ground to a coarse powder. The method of thin-layer chromatography on plates with a layer of silica gel (Sorbfil PTX-AF-A) was used to detect flavonoids and phenolic carboxylic acids. Chromatography was performed in the following mobile phases: ethyl acetate — formic acid anhydrous — water (8:1:1 and 10:2:3), acetic acid 2 and 15%; 0.020% solutions of rutin, quercetin, chlorogenic acid, and caffeic acid in 96% ethanol were used as comparison solutions. To detect sesquiterpene acids, chromatography was performed on plates with a layer of silica gel (Merck TLC Silica gel 60 F254) in the following mobile phases: glacial acetic acid — ethyl acetate — cyclohexane (2:38:60), ethyl acetate — hexane (10:90), acetone — hexane (1:2), hexane — ethyl acetate-glacial acetic acid (65:35:0.5). 0.025% solutions of valerenic acid and acetoxyvaleric acid in 96% ethanol were used as comparison solutions.RESULTS. The conditions of thin-layer chromatography have been selected to separate and identify the chemical components of leaves of Valeriana officinalis, as well as a comparative analysis with biologically active substances of rhizomes with roots of V. officinalis. It was revealed that the leaves of V. officinalis contain flavonoids, tannins and saponins, rhizomes with roots contain phenolic compounds, mainly tannins. The best separation of flavonoids and phenolic carboxylic acids was achieved in the solvent system formic acid anhydrous — water — ethyl acetate (1:1:8). It was found that extracts from the leaves of V. officinalis contain rutin and chlorogenic acid, do not contain quercetin and caffeic acid. The optimal mobile phase for the separation of sesquiterpenic acids from valerian leaf is the glacial acetic acid — ethyl acetate — cyclohexane (2:38:60) system.CONCLUSIONS. It has been established that alcoholic extracts of rhizomes with roots and leaves of valerian have a similar qualitative composition of flavonoids, phenolic carboxylic and sesquiterpenic acids. Rutin, chlorogenic, valerenic, and acetoxyvaleric acids were found in all samples. Thus, V. officinalis leaves can serve as a source of flavonoids, phenolic carboxylic and sesquiterpenic acids.